Age-Related Differences in Structure and Function of Nasal Epithelial Cultures From Healthy Children and Elderly People - Balázs, Anita; Millar-Büchner, Pamela; Mülleder, Michael; Farztdinov, Vadim; Szyrwiel, Lukasz; Addante, Annalisa; Kuppe, Aditi; Rubil, Tihomir; Drescher, Marika; Seidel, Kathrin; Stricker, Sebastian; Eils, Roland; et al. (Frontiers in Immunology, 2022)
The nasal epithelium represents the first line of defense against inhaled pathogens, allergens and irritants and plays a key role in the pathogenesis of a spectrum of acute and chronic airways diseases. Despite age-dependent clinical phenotypes triggered by these noxious stimuli, little is known about how ageing affects the structure and function of the airway epithelium that is crucial for lung homeostasis and host defense. The aim of this study was therefore to determine age-related differences in structural and functional properties of primary nasal epithelial cultures from healthy children and non-smoking elderly people. To achieve this goal, highly differentiated nasal epithelial cultures were established from nasal brushes at air-liquid-interface and used to study epithelial cell type composition, mucin (MUC5AC and MUC5B) expression and ion transport properties. Further, we determined age-dependent molecular signatures using global proteomic analysis. We found lower numeric densities of ciliated cells and higher levels of MUC5AC expression in cultures from children vs. elderly people. Bioelectric studies showed no differences in basal ion transport properties, ENaC-mediated sodium absorption or CFTR-mediated chloride transport, but detected decreased calcium-activated TMEM16A-mediated chloride secretory responses in cultures from children vs. elderly people. Proteome analysis identified distinct age-dependent molecular signatures associated with ciliation and mucin biosynthesis, as well as other pathways implicated in ageing. Our data identified intrinsic, age-related differences in structure and function of the nasal epithelium and provide a basis for further studies on the role of these findings in age-dependent airways disease phenotypes observed with a spectrum of respiratory infections and other noxious stimuli.